Blocked and random practice organization in the learning of rhythmic dance step sequences - Bertollo, M.; Berchicci, M.; Carraro, A.; Comani, S.; Robazza, C. (Perceptual and Motor Skills, 2010)
This study investigated the role played by Blocked (low contextual interference) and Random (high contextual interference) schedules in the acquisition of rhythmic footstep sequences by adolescent females (N = 40, M age = 15.8 yr., SD = 1.3). After a baseline assessment (T0), motor learning was assessed after six sessions (T1) in terms of the participants` ability to reproduce the step sequences using visual and auditory guidance. A retention test (T2) also occurred 21 days after T1. Analysis of variance yielded significant main effects of group, test, and an interaction. Both groups improved performance from T0 to T1, but the Blocked schedule group outperformed the Random schedule group at T1. Significant group differences were not observed at T2. The Random schedule group's performance did not significantly change from T1 to T2, and the Blocked schedule group's performance significantly decreased. Apparently, the learning of rhythmic footstep dance sequences was not influenced by practice organization.